Statistical Optimization of Bioleaching for Simultaneous Recovery of Cu, Sn, Pb, and Zn from Computer-Printed Circuit Boards - Murugesan Manikkampatti Palanisamy; Venkata Ratnam Myneni; Akilamudhan Palaniappan; Padmapriya Veerappan; Minar Mohamed Lebbai; G. Kavitha (Journal of Chemistry)
Electronic garbage is one of the fastest-growing waste streams. Its disposal and appropriate management are a worldwide concern. Printed circuit boards (PCBs) are critical components in contemporary electronic gadgets that contain toxic elements. Bioprocessing of PCBs for metal recovery employing microbial methods has evolved as a green solution in metallurgical operations. Acidithiobacillus ferrooxidans and Acidithiobacillus thiooxidans were used in this study to leach metals from powdered waste PCBs. The RSM is used for optimizing the leaching conditions. The optimal conditions obtained were a bacterial activation period of 28 days, a pulp density of 23 g/L, and a temperature of 31°C. A confirmatory experiment under these optimal circumstances yielded recovery rates of Cu2+, Sn2+, Pb2+, and Zn2+ of 95.62%, 96.27%, 95.6%, and 98.25%, respectively.